Analisis Faktor yang Mempengaruhi Turnover Intention di PT. XYZ - Zulfadli Hamzah (Journal of Economic, Bussines and Accounting (COSTING), 2019)
Managing a company is not something that is easy, there are many obstacles that might be faced in creating a quality and competent company, especially managing people within the company. This study aims to determine the effect of leadership and motivation on turnover intention at the PT. XYZ. Analysis was carried out on 32 respondents, this study was taken by census method and data was collected through questionnaires. The data analysis technique used is multiple linear regression through T test statistics and test models (F and Coefficient of reflection). The results showed that the overall leadership and motivation variables partially or simultaneously had an effect on turnover intention. Keywords: Leadership, Motivation, Turnover Intention